Effect of gurney flaps on the performance of a vertical axis wind turbine under icing condition - Hexiang Yu; Zhehui Zheng; Pei Yang (Center of Biomass & Renewable Energy (CBIORE), 2026)
To investigate the operational characteristics of a vertical-axis wind turbine equipped with Gurney flap blades in icy conditions, the study employs the pitching and sinking movements of an individual blade to replicate the cyclic oscillations experienced by a vertical-axis wind turbine (VAWT) blade during rotation at a temperature of 265K. The aim is to analyze the icing pattern and assess the performance of the wind turbine with varying tip-speed ratios of Gurney flap blades. The findings indicate that as icing time increases, the vertical axis wind turbine experiences a significant decrease in output power. This is attributed to the formation of a leading-edge ice angle, which generates a leading-edge vortex and exacerbates flow separation, consequently reducing the wind turbine's torque coefficient. After 6 minutes of icing, the power coefficient decreases by up to 81%. Additionally, the Gurney flap blades develop ice accumulation on the flaps, which reduces their effectiveness in preventing flow separation. Specifically, when the tip speed ratio of the blade is 3.5, it is observed that the icing on the Gurney flap blades is less effective after 6 minutes compared to that on the VAWT. At a tip speed ratio of 3.5, the vertical axis wind turbine (VAWT) with Gurney flaps ceases to function properly after 6 minutes, leading to a decrease in output power to -0.012. However, within the tip speed range of 1.5 to 3, the Gurney flaps continue to serve as a means of flow control. They enhance the wind turbine's resistance to loss in icing conditions when compared to the original airfoil vertical axis wind turbine under similar operational circumstances.